Michael J. answered • 07/27/16

Tutor

5
(5)
Effective High School STEM Tutor & CUNY Math Peer Leader

Let Cayle's height = x

Let Morgan's height = (1/2)x

Let Jane's height = x - 1

Using these variables, we can create an equation that represents the average of their heights. Average is the sum of the heights divided by the number of heights.

Convert average height to feet to be consistent with units. The heights of the 3 people are in feet.

6 feet 1 inch = 6 1/12 feet = 73/12 feet

Now we create the equation and solve for x.

**[**x + (1/2)x + x - 1

**]**/ 3

**=**73 / 12

(2.5x - 1) / 3 = 73 / 12

Multiply both sides of equation by 3.

2.5x - 1 = 73 / 4

Multiply both sides of equation by 4.

10x - 4 = 73

10x = 77

x = 7.7

Plug in this value of x into the variables to get the 3 heights.